Curable resin composition, dry film, cured product and printed wiring board
By adding alkali-soluble resin, photopolymerization initiator and thermosetting resin to the hardening resin composition, combined with appropriate pigments, the problem of oxidation and discoloration of copper circuits is solved, and the balance of high resolution and hidden effects is achieved, and the appearance quality of the printed circuit board is improved.
Patent Information
- Application Number
- JP2024197721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-04-14
AI Technical Summary
The existing hardened resin composition cannot effectively hide the oxidation and discoloration problem of copper circuits in IC packaging, and it is easy to cause the copper circuit to develop during the thermal curing process, affecting the appearance of the printed circuit board, and the existing resin composition is difficult to balance between high resolution and hidden effects.
A resin composition containing an alkali-soluble resin, a photopolymerization initiator, a thermosetting resin and a pigment is used to form a hardened film with good hiddenness and high resolution on the copper surface by adjusting the light transmittance within a specific wavelength range.
The copper circuit color changes small after heat treatment and has a high resolution hidden effect, which improves the appearance quality of the printed circuit board.
Smart Images

Figure 2025015597000001 
Figure 2025015597000002 
Figure 2025015597000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a curable resin composition, a dry film, a cured product, and a printed wiring board. [Background technology]
[0002] In the manufacture of printed wiring boards, curable resin compositions are generally used to form permanent coatings such as solder resists, and dry film-type compositions and liquid compositions have been developed as such curable resin compositions. Among these, due to consideration of environmental issues, alkaline development-type curable resin compositions that use a dilute alkaline aqueous solution as a developer have become mainstream, and several composition systems have been proposed (for example, Patent Document 1).
[0003] Rapid advances in semiconductor components have led to a trend toward lighter, thinner, smaller, higher performance, and more multifunctional electronic devices. Following this trend, miniaturization and increased pin counts in semiconductor packages have been commercialized. Specifically, IC packages known as QFP (quad flat pack package) and SOP (small outline package) are being replaced by IC packages known as BGA (ball grid array) and CSP (chip scale package). Furthermore, FC-BGA (flip chip ball grid array) has also recently been commercialized as an even higher-density IC package. Permanent coatings such as solder resists applied to the printed wiring boards (also known as package substrates) used in these IC packages require ever thinner thicknesses. Furthermore, from the viewpoint of hiding power and design, solder resists are sometimes required to be black. For this reason, curable resin compositions used for solder resists include those containing carbon black as a colorant, which gives the solder resist its black color, and those containing a combination of pigments of multiple colors other than black, which gives the solder resist its black color. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 61-243869 A (Claims) Summary of the Invention [Problem to be solved by the invention]
[0005] Current solder resists are often photocured to form images, followed by a final thermal curing process. This thermal curing process can cause discoloration of the copper circuit due to oxidation. Furthermore, when marking ink is applied to a substrate, the marking is printed and thermally cured after the solder resist has cured, which can accelerate discoloration of the copper circuit. Furthermore, pressure and heat may be applied to correct warpage of the substrate that occurs during thermal curing of the solder resist, which can also discolor the circuit. Conventional black curable resin compositions have been unable to completely conceal this discoloration, resulting in a poor appearance of the substrate. Furthermore, conventional curable resin compositions containing a blue colorant to achieve a black color in combination with the copper color of the copper circuit also lack sufficient hiding power. In particular, there is still room for improvement in the hiding power of copper circuits that have undergone CZ treatment, a process to roughen the copper surface and improve adhesion. Furthermore, solder resist must avoid as much as possible any reduction in resolution due to the incorporation of colorants, and is required to achieve both high levels of hiding power and resolution. However, in the past, it was necessary to change components other than the color tone, and if priority was given to resolution, it was necessary to reduce the amount of black pigment added, which ensures hiding power. In this case, depending on the curing conditions, the color tone would change due to oxidation of the copper circuit.
[0006] Therefore, an object of the present invention is to provide an alkali-developable curable resin composition that forms a coating film on copper after CZ treatment that has excellent hiding properties and therefore changes little in color after heating, and that has excellent resolution; a dry film having a resin layer obtained from the composition; a cured product of the composition or the resin layer of the dry film; and a printed wiring board having the cured product. [Means for solving the problem]
[0007] In view of the above, the present inventors have conducted extensive research and have found that a curable resin composition having a transmittance within a predetermined range under specific test conditions provides a coating film formed on copper after CZ treatment with excellent hiding properties, resulting in little change in color after heating and excellent resolution, and have thus completed the present invention.
[0008] That is, the curable resin composition of the present invention contains (A) an alkali-soluble resin, (B) a photopolymerization initiator, (C) a thermosetting resin, and (D) a colorant, and is formed on copper having a CZ-treated surface, The curable resin composition is characterized in that the dry coating film (20 μm thick) formed on a 2 mm thick glass substrate has a transmittance of 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm.
[0009] In the curable resin composition of the present invention, the dry coating film preferably has a transmittance of 12% or less at a wavelength of 720 nm.
[0010] The curable resin composition of the present invention preferably has a transmittance of 5% or more at a wavelength of 365 nm when the dried coating film is coated.
[0011] The dry film of the present invention is characterized by having a resin layer obtained from the curable resin composition.
[0012] The cured product of the present invention is characterized by being obtained by curing the curable resin composition or the resin layer of the dry film.
[0013] The printed wiring board of the present invention is characterized by comprising the above-described cured product. [Effects of the Invention]
[0014] According to the present invention, it is possible to provide an alkali-developable curable resin composition that forms a coating film on copper after CZ treatment that has excellent hiding properties and therefore changes little in color after heating, and that has excellent resolution; a dry film having a resin layer obtained from the composition; a cured product of the composition or the resin layer of the dry film; and a printed wiring board having the cured product. DETAILED DESCRIPTION OF THE INVENTION
[0015] The curable resin composition of the present invention contains (A) an alkali-soluble resin, (B) a photopolymerization initiator, (C) a thermosetting resin, and (D) a colorant, and is formed on copper having a CZ-treated surface, The transmittance of a dried coating film (20 μm thick) of the curable resin composition formed on a 2 mm thick glass substrate is 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm. In one example, the blending ratios of the red, yellow, blue, and black colorants in the curable resin composition are adjusted so that the coating film tested on a 2 mm thick glass substrate has a transmittance of 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm. A curable resin composition having such a transmittance is neither a conventional black curable resin composition nor a conventional blue curable resin composition, but a novel curable resin composition. Although it is difficult to specify the transmittance based on the blending ratio of the colorant, a curable resin composition having a dry coating film (film thickness 20 μm) of the curable resin composition formed on a 2 mm thick glass substrate and having a transmittance of 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm combines the hiding power and resolution desired in the present invention. Therefore, the curable resin composition of the present invention is specified to have a transmittance within a predetermined range under specific test conditions. The transmittance was measured by forming a dry coating film of 20 μm thick on a 2 mm thick glass substrate using an applicator after drying at 80°C for 30 minutes, or by laminating a 20 μm thick dry film on a 2 mm thick glass substrate and peeling off the carrier film, using a UV-Visible-Near-Infrared Spectrophotometer V-670 (manufactured by JASCO Corporation). Preferably, the transmittance of the dried coating film is 12% or less at a wavelength of 720 nm, which makes it possible to minimize changes in color tone after heat treatment. Preferably, the transmittance of the dried coating film is 5% or more at a wavelength of 365 nm, which can improve the resolution.
[0016] Each component of the curable resin composition of the present invention will be described below. In this specification, the term "(meth)acrylate" is a general term that refers to acrylate, methacrylate, and mixtures thereof, and the same applies to other similar expressions.
[0017] [(A) Alkali-soluble resin] Examples of (A) alkali-soluble resins include compounds having two or more phenolic hydroxyl groups, carboxyl group-containing resins, compounds having a phenolic hydroxyl group and a carboxyl group, and compounds having two or more thiol groups. Among these, a carboxyl group-containing resin or a phenolic resin is preferred as the alkali-soluble resin, since it improves adhesion to the substrate. In particular, the alkali-soluble resin is more preferably a carboxyl group-containing resin, since it has excellent developability. The carboxyl group-containing resin is preferably a carboxyl group-containing photosensitive resin having an ethylenically unsaturated double bond, but may also be a carboxyl group-containing resin without an ethylenically unsaturated double bond.
[0018] Specific examples of the carboxyl group-containing resin include the compounds (which may be either oligomers or polymers) listed below.
[0019] (1) Carboxyl group-containing resins obtained by copolymerizing unsaturated carboxylic acids such as (meth)acrylic acid with unsaturated group-containing compounds such as styrene, α-methylstyrene, lower alkyl (meth)acrylates, and isobutylene.
[0020] (2) Carboxylic acid-containing urethane resins obtained by the polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl-containing dialcohol compounds such as dimethylolpropionic acid and dimethylolbutanoic acid, and diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.
[0021] (3) Terminal carboxyl group-containing urethane resins obtained by reacting acid anhydrides with the terminals of urethane resins obtained by polyaddition reaction of diisocyanate compounds such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.
[0022] (4) Carboxylic acid group-containing urethane resins obtained by the polyaddition reaction of diisocyanates with (meth)acrylates of bifunctional epoxy resins such as bisphenol A epoxy resins, hydrogenated bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bixylenol epoxy resins, and biphenol epoxy resins, or their partially acid anhydride-modified products, carboxylic acid group-containing dialcohol compounds, and diol compounds.
[0023] (5) A carboxyl group-containing urethane resin that is (meth)acrylated at the terminal by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as hydroxyalkyl (meth)acrylate, during the synthesis of the resin (2) or (4) above.
[0024] (6) A carboxyl group-containing urethane resin that is (meth)acrylated at the terminal by adding a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate, during the synthesis of the resin (2) or (4) above.
[0025] (7) A carboxyl group-containing resin obtained by reacting a multifunctional epoxy resin with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl groups present in the side chains.
[0026] (8) A carboxyl group-containing resin obtained by reacting a polyfunctional epoxy resin in which the hydroxyl groups of a difunctional epoxy resin have been further epoxidized with epichlorohydrin with (meth)acrylic acid, and then adding a dibasic acid anhydride to the resulting hydroxyl groups.
[0027] (9) A carboxyl group-containing polyester resin obtained by reacting a polyfunctional oxetane resin with a dicarboxylic acid and adding a dibasic acid anhydride to the resulting primary hydroxyl group.
[0028] (10) A carboxyl group-containing resin obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with an alkylene oxide such as ethylene oxide or propylene oxide, reacting the resulting reaction product with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.
[0029] (11) A carboxyl group-containing resin obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, reacting the resulting reaction product with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.
[0030] (12) A carboxyl group-containing resin obtained by reacting an epoxy compound having multiple epoxy groups in one molecule with a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule, such as p-hydroxyphenethyl alcohol, and an unsaturated group-containing monocarboxylic acid, such as (meth)acrylic acid, and then reacting the alcoholic hydroxyl groups of the resulting reaction product with a polybasic acid anhydride, such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, or adipic anhydride.
[0031] (13) A carboxyl group-containing resin obtained by further adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule, such as glycidyl (meth)acrylate, α-methylglycidyl (meth)acrylate, etc., to the carboxyl group-containing resin described in (1) to (12) above.
[0032] Among the above carboxyl group-containing resins, the carboxyl group-containing resins described in (1), (7), (8), and (10) to (13) are preferred.
[0033] Examples of compounds having a phenolic hydroxyl group include compounds having a biphenyl skeleton, a phenylene skeleton, or both of these skeletons, and phenolic resins having various skeletons synthesized using phenol, orthocresol, para-cresol, meta-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, catechol, resorcinol, hydroquinone, methylhydroquinone, 2,6-dimethylhydroquinone, trimethylhydroquinone, pyrogallol, phloroglucinol, etc.
[0034] Examples of the compound having a phenolic hydroxyl group include known and commonly used phenolic resins such as phenol novolac resin, alkylphenol volac resin, bisphenol A novolac resin, dicyclopentadiene-type phenolic resin, Xylok-type phenolic resin, terpene-modified phenolic resin, polyvinylphenols, bisphenol F, bisphenol S-type phenolic resin, poly-p-hydroxystyrene, condensates of naphthol and aldehydes, and condensates of dihydroxynaphthalene and aldehydes.
[0035] Commercially available phenolic resins include, for example, HF1H60 (manufactured by Meiwa Chemical Industry Co., Ltd.), Phenolite TD-2090, Phenolite TD-2131 (manufactured by DIC Corporation), Besumor CZ-256-A (manufactured by DIC Corporation), Shounol BRG-555, Shounol BRG-556 (manufactured by Aica Kogyo Co., Ltd.), and polyvinylphenols CST70, CST90, S-1P, and S-2P (manufactured by Maruzen Oil Co., Ltd.).
[0036] The acid value of the alkali-soluble resin (A) is preferably in the range of 40 to 200 mgKOH / g, more preferably 45 to 120 mgKOH / g. When the acid value of the alkali-soluble resin is 40 mgKOH / g or more, alkaline development becomes easy, while when it is 200 mgKOH / g or less, drawing of a normal resist pattern becomes easy, so this is preferable.
[0037] The weight-average molecular weight of the alkali-soluble resin (A) varies depending on the resin skeleton, but is preferably in the range of 1,500 to 150,000, and more preferably 1,500 to 100,000. When the weight-average molecular weight is 1,500 or more, the tack-free performance is good, the moisture resistance of the coating film after exposure is good, film loss during development is suppressed, and a decrease in resolution can be suppressed. On the other hand, when the weight-average molecular weight is 150,000 or less, the developability is good and storage stability is also excellent.
[0038] The alkali-soluble resin (A) can be used alone or in combination of two or more.
[0039] [(B) Photopolymerization initiator] In the curable resin composition of the present invention, any photopolymerization initiator known as a photopolymerization initiator or a photoradical generator can be used as the photopolymerization initiator (B). Examples of the photopolymerization initiator (B) include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, and bis-(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad, manufactured by IGM Resins). 819), and other bisacylphosphine oxides; 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphine acid methyl ester, 2-methylbenzoyldiphenylphosphine oxide, pivaloylphenylphosphinic acid isopropyl ester, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO manufactured by IGM Resins), Monoacylphosphine oxides such as H); hydroxyacetophenones such as 1-hydroxycyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and 2-hydroxy-2-methyl-1-phenylpropan-1-one; benzoins such as benzoin, benzil, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, and benzoin n-butyl ether; benzoin alkyl ethers;Benzophenones such as benzophenone, p-methylbenzophenone, Michler's ketone, methylbenzophenone, 4,4'-dichlorobenzophenone, and 4,4'-bisdiethylaminobenzophenone; acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, and 2-benzyl-2 -dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone, and other acetophenones; thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2,4-diisopropylthioxanthone, and other thioxanthones; Anthraquinones such as anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, and 2-aminoanthraquinone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzoic acid esters such as ethyl 4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and p-dimethylbenzoic acid ethyl ester; 1,2-octanedione, 1-[4 -(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), and other oxime esters; bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1-pyr-1-yl)ethyl)phenyl]titanium, and other titanocenes;Examples of suitable photopolymerization initiators include phenyl disulfide, 2-nitrofluorene, butyroin, anisoin ethyl ether, azobisisobutyronitrile, and tetramethylthiuram disulfide. One photopolymerization initiator may be used alone, or two or more may be used in combination. Among these, oxime esters (hereinafter also referred to as "oxime ester-based photopolymerization initiators") are preferred, with ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, and 1-(O-acetyloxime) being more preferred. The amount of the (B) photopolymerization initiator is, for example, 0.01 to 30 parts by mass per 100 parts by mass of the solid content of the (A) alkali-soluble resin. The amount of the oxime ester photopolymerization initiator is preferably 8% by mass or more, more preferably 12% by mass or more, calculated as solid content, based on the total amount of photopolymerization initiator. High sensitivity can be easily achieved by including 8% by mass or more of the oxime ester photopolymerization initiators. One type of oxime ester photopolymerization initiator can be used alone, or two or more types can be used in combination.
[0040] Any known oxime ester photopolymerization initiator can be used as the oxime ester photopolymerization initiator. Commercially available products include Irgacure OXE01 (1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)]) and Irgacure OXE02 (ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime)) manufactured by BASF Japan, N-1919 and NCI-831 manufactured by ADEKA, and TR-PBG-304 manufactured by Changzhou Power Electronics New Materials Co., Ltd.
[0041] Furthermore, initiators having two oxime ester groups in the molecule can also be suitably used, and specific examples thereof include oxime ester compounds having a carbazole structure represented by the following general formula: TIFF2025015597000001.tif48170 (wherein X represents a hydrogen atom, an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a phenyl group, a phenyl group (substituted with an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having an alkyl group of 1 to 8 carbon atoms, or a dialkylamino group), a naphthyl group (substituted with an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having an alkyl group of 1 to 8 carbon atoms, or a dialkylamino group), and Y and Z represent a hydrogen atom, an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a halogen group, a phenyl group, a phenyl group (substituted with an alkylamino group having 1 to 17 carbon atoms, or a dialkylamino group), Ar represents a bond or an alkylene having 1 to 10 carbon atoms, vinylene, phenylene, biphenylene, pyridylene, naphthylene, thiophene, anthrylene, thienylene, furylene, 2,5-pyrrole-diyl, 4,4'-stilbene-diyl, or 4,2'-styrene-diyl, and n is an integer of 0 or 1.
[0042] In particular, in the general formula, it is preferred that X and Y are each a methyl group or an ethyl group, Z is a methyl group or a phenyl group, n is 0, and Ar is a bond, phenylene, naphthylene, thiophene, or thienylene.
[0043] Further, preferred carbazole oxime ester compounds include compounds represented by the following general formula: TIFF2025015597000002.tif52170 (in the formula, R 1represents an alkyl group having 1 to 4 carbon atoms, or a phenyl group which may be substituted with a nitro group, a halogen atom or an alkyl group having 1 to 4 carbon atoms. R 2 represents an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a phenyl group which may be substituted with an alkyl group or an alkoxy group having 1 to 4 carbon atoms. R 3 represents an alkyl group having 1 to 20 carbon atoms which may be linked via an oxygen atom or a sulfur atom and which may be substituted with a phenyl group, or a benzyl group which may be substituted with an alkoxy group having 1 to 4 carbon atoms. R 4 represents a nitro group or an acyl group represented by XC(=O)-, where X represents an aryl group optionally substituted with an alkyl group having 1 to 4 carbon atoms, a thienyl group, a morpholino group, a thiophenyl group, or a structure represented by the following formula: TIFF2025015597000003.tif18170
[0044] Other examples include carbazole oxime ester compounds described in JP-A Nos. 2004-359639, 2005-097141, 2005-220097, 2006-160634, 2008-094770, JP-T Nos. 2008-509967, 2009-040762, and 2011-80036.
[0045] [(C) Thermosetting resin] The curable resin composition of the present invention is expected to have improved heat resistance due to the inclusion of a thermosetting resin. The thermosetting resin may be used alone or in combination of two or more. Any known thermosetting resin may be used. For example, known thermosetting resins such as amino resins, such as melamine resins, benzoguanamine resins, melamine derivatives, and benzoguanamine derivatives, isocyanate compounds, blocked isocyanate compounds, cyclocarbonate compounds, epoxy compounds, oxetane compounds, episulfide resins, bismaleimides, and carbodiimide resins may be used. Particularly preferred are thermosetting resins having multiple cyclic ether groups or cyclic thioether groups (hereinafter abbreviated as cyclic (thio)ether groups) in the molecule.
[0046] The thermosetting resin having multiple cyclic (thio)ether groups in the molecule is a compound having multiple 3-, 4-, or 5-membered cyclic (thio)ether groups in the molecule, and examples thereof include a compound having multiple epoxy groups in the molecule, i.e., a polyfunctional epoxy compound; a compound having multiple oxetanyl groups in the molecule, i.e., a polyfunctional oxetane compound; and a compound having multiple thioether groups in the molecule, i.e., an episulfide resin.
[0047] Examples of polyfunctional epoxy compounds include epoxidized vegetable oils, bisphenol A epoxy resins, hydroquinone epoxy resins, bisphenol epoxy resins, thioether epoxy resins, brominated epoxy resins, novolac epoxy resins, biphenol novolac epoxy resins, bisphenol F epoxy resins, hydrogenated bisphenol A epoxy resins, glycidylamine epoxy resins, hydantoin epoxy resins, alicyclic epoxy resins, trihydroxyphenylmethane epoxy resins, bixylenol or biphenol epoxy resins, or mixtures thereof. Examples of epoxy resins include, but are not limited to, bisphenol S epoxy resins, bisphenol A novolac epoxy resins, tetraphenylolethane epoxy resins, heterocyclic epoxy resins, diglycidyl phthalate resins, tetraglycidyl xylenoylethane resins, naphthalene group-containing epoxy resins, epoxy resins having a dicyclopentadiene skeleton, glycidyl methacrylate copolymer epoxy resins, cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resins, epoxy-modified polybutadiene rubber derivatives, and CTBN-modified epoxy resins. These epoxy resins can be used alone or in combination of two or more. Among these, novolac epoxy resins, bisphenol epoxy resins, bixylenol epoxy resins, biphenol epoxy resins, biphenol novolac epoxy resins, naphthalene epoxy resins, and mixtures thereof are particularly preferred.
[0048] Examples of polyfunctional oxetane compounds include bis[(3-methyl-3-oxetanylmethoxy)methyl]ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl]ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methyl acrylate, and (3-ethyl-3-oxetanyl)methyl acrylate. Examples of suitable oxetane compounds include polyfunctional oxetanes such as acrylate, (3-methyl-3-oxetanyl)methyl methacrylate, (3-ethyl-3-oxetanyl)methyl methacrylate, and their oligomers or copolymers, as well as ethers of oxetane alcohols with novolak resins, poly(p-hydroxystyrene), cardo-type bisphenols, calixarenes, calixresorcinarenes, or hydroxyl group-containing resins such as silsesquioxane. Other examples include copolymers of unsaturated monomers having an oxetane ring and alkyl (meth)acrylates.
[0049] Examples of compounds having multiple cyclic thioether groups in the molecule include bisphenol A episulfide resins. Furthermore, episulfide resins in which the oxygen atoms of the epoxy groups of novolac epoxy resins are replaced with sulfur atoms using a similar synthesis method can also be used. The amount of such thermosetting resins having multiple cyclic (thio)ether groups in the molecule is preferably 0.6 to 2.5 equivalents, more preferably 0.8 to 2.0 equivalents, of the cyclic (thio)ether groups per equivalent of the alkali-soluble groups, such as carboxyl groups and phenolic hydroxyl groups, of the alkali-soluble resin (A).
[0050] Examples of amino resins such as melamine derivatives and benzoguanamine derivatives include methylolmelamine compounds, methylolbenzoguanamine compounds, methylolglycoluril compounds, and methylolurea compounds.
[0051] The isocyanate compound may be a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, naphthalene-1,5-diisocyanate, o-xylylene diisocyanate, m-xylylene diisocyanate, and 2,4-tolylene dimer; aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate), and isophorone diisocyanate; alicyclic polyisocyanates such as bicycloheptane triisocyanate; and adducts, biuret compounds, and isocyanurates of the above-mentioned isocyanate compounds.
[0052] The blocked isocyanate compound can be an addition reaction product of an isocyanate compound and an isocyanate blocking agent. Examples of isocyanate compounds that can react with an isocyanate blocking agent include the polyisocyanate compounds described above. Examples of the isocyanate blocking agent include phenol-based blocking agents, lactam-based blocking agents, active methylene-based blocking agents, alcohol-based blocking agents, oxime-based blocking agents, mercaptan-based blocking agents, acid amide-based blocking agents, imide-based blocking agents, amine-based blocking agents, imidazole-based blocking agents, and imine-based blocking agents.
[0053] The thermosetting resins can be used alone or in combination of two or more. The amount of the thermosetting resin is preferably 20 to 60 parts by mass, more preferably 30 to 50 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When the amount is 20 parts by mass or more, excellent heat resistance is achieved. When the amount is 60 parts by mass or less, storage stability is improved.
[0054] [(D) Colorant] The colorant may be one or more of a red colorant, a green colorant, a blue colorant, a yellow colorant, a white colorant, a black colorant, or other colorants, in appropriate combination. It may be any of a pigment, a dye, and a coloring matter. Specific examples include those assigned a Color Index (CI; published by The Society of Dyers and Colorists) number. However, from the viewpoint of reducing environmental impact and impact on the human body, a colorant that does not contain halogen is preferred.
[0055] Examples of red colorants include monoazo-based, dizazo-based, azo-lake-based, benzimidazolone-based, perylene-based, diketopyrrolopyrrole-based, condensed azo-based, anthraquinone-based, and quinacridone-based. Green colorants include similarly metal-substituted or unsubstituted phthalocyanines, anthraquinones, and perylenes. The blue colorant may be any of pigments, dyes, and coloring matters, but among them, those that do not contain halogen atoms are preferred. Blue colorants include phthalocyanine-based and anthraquinone-based, and pigment-based compounds are classified as pigments, specifically, the following: Examples include: Pigment Blue 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, 60. Dye-based pigments include Solvent Blue 35, 63, 68, 70, 83, 87, 94, 97, 122, 136, 67, and 70. In addition to the above, metal-substituted or unsubstituted phthalocyanine compounds can also be used. The blue colorant may be used alone or in combination of two or more. Examples of yellow colorants include monoazo-based, disazo-based, condensed azo-based, benzimidazolone-based, isoindolinone-based, and anthraquinone-based colorants. Examples of the white colorant include rutile and anatase titanium oxides. Examples of black colorants include titanium black, carbon black, graphite, iron oxide, anthraquinone, cobalt oxide, copper oxide, manganese, antimony oxide, nickel oxide, perylene, and aniline pigments, molybdenum sulfide, and bismuth sulfide. In addition, colorants such as purple, orange, brown, etc. may be added to adjust the color tone. In order to obtain an alkali-developable curable resin composition that has excellent resolution and in which the coating film formed on copper after the CZ treatment has excellent hiding power and therefore undergoes little change in color after heating, it is preferable to combine a red colorant, a yellow colorant, a blue colorant, and a black colorant as the colorant. In this case, the blending amounts of the (D) colorant are preferably within the ranges of 0.01 to 0.04 parts by mass of the black colorant, 1.10 to 2.45 parts by mass of the blue colorant, 0.01 to 0.08 parts by mass of the yellow colorant, and 0.60 to 2.00 parts by mass of the red colorant, relative to 100 parts by mass of the solids content of the (A) alkali-soluble resin, and more preferably within the ranges of 0.02 to 0.03 parts by mass of the black colorant, 1.40 to 2.20 parts by mass of the blue colorant, 0.03 to 0.06 parts by mass of the yellow colorant, and 0.75 to 1.20 parts by mass of the red colorant.
[0056] [Inorganic filler] The curable resin composition of the present invention preferably contains an inorganic filler. The inorganic filler is not particularly limited, and known and commonly used inorganic fillers such as silica, crystalline silica, Neuburg silica, aluminum hydroxide, glass powder, talc, clay, magnesium carbonate, calcium carbonate, natural mica, synthetic mica, aluminum hydroxide, barium sulfate, barium titanate, iron oxide, non-fibrous glass, hydrotalcite, mineral wool, aluminum silicate, calcium silicate, and zinc oxide can be used alone or in combination of two or more. Among these, silica is preferred, and spherical silica is more preferred because it has a small surface area and distributes stress throughout, making it less likely to become a starting point for cracks.
[0057] The inorganic filler may be surface-treated. Here, the surface treatment of the inorganic filler refers to a treatment to improve compatibility with the resin component. The surface treatment of the inorganic filler may be a surface treatment that introduces a curable reactive group to the surface of the inorganic filler, or may not introduce a curable reactive group. Here, the curable reactive group is not particularly limited as long as it is a group that undergoes a curing reaction with a curable compound such as (A) an alkali-soluble resin or (C) a thermosetting resin, and may be a curable reactive group or a thermosetting reactive group. Examples of the curable reactive group include a methacrylic group, an acrylic group, a vinyl group, and a styryl group. Examples of the thermosetting reactive group include an epoxy group, an amino group, a hydroxyl group, a carboxyl group, an isocyanate group, an imino group, an oxetanyl group, a mercapto group, a methoxymethyl group, a methoxyethyl group, an ethoxymethyl group, an ethoxyethyl group, and an oxazoline group. The method for introducing curable reactive groups onto the surface of the inorganic filler is not particularly limited, and may be carried out using a known, commonly used method. The surface of the inorganic filler may be treated with a surface treatment agent having a curable reactive group, such as a coupling agent having a curable reactive group as an organic group. Examples of the coupling agent include a silane coupling agent, a titanium coupling agent, a zirconium coupling agent, and an aluminum coupling agent. Examples of surface-treated inorganic fillers that do not have curable reactive groups include inorganic fillers that have been surface-treated with silica-alumina, titanate-based coupling agents, aluminate-based coupling agents, or organically treated.
[0058] The inorganic filler can be used alone or in combination of two or more. The amount of inorganic filler to be added is preferably 80 to 450 parts by mass, more preferably 100 to 200 parts by mass, per 100 parts by mass of the solid content of (A) the alkali-soluble resin. When the amount is 80 parts by mass or more, excellent heat resistance is achieved. When the amount is 450 parts by mass or less, even better resolution is achieved.
[0059] (Compounds having an ethylenically unsaturated group) The curable resin composition of the present invention may contain, unlike the alkali-soluble resin (A), a substance that functions as a reactive diluent, specifically, a compound having an ethylenically unsaturated group. As the compound having an ethylenically unsaturated group, a photopolymerizable oligomer, a photopolymerizable vinyl monomer, or the like, which is a known and commonly used photocurable monomer, may be used.
[0060] Examples of the photopolymerizable oligomer include unsaturated polyester oligomers, (meth)acrylate oligomers, etc. Examples of the (meth)acrylate oligomer include epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and bisphenol-type epoxy (meth)acrylate, urethane (meth)acrylate, epoxy urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and polybutadiene-modified (meth)acrylate.
[0061] Examples of the photopolymerizable vinyl monomer include known and commonly used ones, for example, styrene derivatives such as styrene, chlorostyrene, and α-methylstyrene; vinyl esters such as vinyl acetate, vinyl butyrate, and vinyl benzoate; vinyl ethers such as vinyl isobutyl ether, vinyl-n-butyl ether, vinyl-t-butyl ether, vinyl-n-amyl ether, vinyl isoamyl ether, vinyl-n-octadecyl ether, vinyl cyclohexyl ether, ethylene glycol monobutyl vinyl ether, and triethylene glycol monomethyl vinyl ether; (meth)acrylamides such as acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and N-butoxymethyl acrylamide; allyl compounds such as triallyl isocyanurate, diallyl phthalate, and diallyl isophthalate; 2-ethylhexyl (meth)acrylate, lauryl ( (Meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate and other (meth)acrylic acid esters; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate and other hydroxyalkyl (meth)acrylates; methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate and other alkoxyalkylene glycol mono(meth)acrylates; ethylene glycol di(meth)acrylate, butanediol di(meth)acrylates, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate and other alkylene polyol poly(meth)acrylates;Examples include polyoxyalkylene glycol poly(meth)acrylates such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, ethoxylated trimethylolpropane triacrylate, and propoxylated trimethylolpropane tri(meth)acrylate; poly(meth)acrylates such as hydroxypivalic acid neopentyl glycol ester di(meth)acrylate; and isocyanurate-type poly(meth)acrylates such as tris[(meth)acryloxyethyl]isocyanurate. These may be used alone or in combination of two or more types depending on the required properties.
[0062] The compound having an ethylenically unsaturated group can be used alone or in combination of two or more. The amount of the compound having an ethylenically unsaturated group is preferably 3 to 25 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When it is 3 parts by mass or more, it contributes to high sensitivity. When it is 25 parts by mass or less, the resolution is improved.
[0063] (Thermosetting catalyst) The curable resin composition of the present invention may contain a thermosetting catalyst. Examples of such a thermosetting catalyst include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine compounds such as adipic acid dihydrazide and sebacic acid dihydrazide; and phosphorus compounds such as triphenylphosphine. In addition, S-triazine derivatives such as guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-S-triazine, 2-vinyl-2,4-diamino-S-triazine, 2-vinyl-4,6-diamino-S-triazine-isocyanuric acid adduct, and 2,4-diamino-6-methacryloyloxyethyl-S-triazine-isocyanuric acid adduct can also be used, and these compounds that also function as adhesion promoters are preferably used in combination with the thermosetting catalyst. Furthermore, organic fillers can also be used as long as they can be used as thermosetting catalysts.
[0064] As the thermosetting catalyst, an organic filler having an amino group is preferred, and specifically, at least one of melamine and dicyandiamide (DICY) is preferred.
[0065] The thermosetting catalyst can be used alone or in combination of two or more. The amount of the thermosetting catalyst is preferably 0.5 to 10 parts by mass, more preferably 1 to 8 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When the amount is 0.5 parts by mass or more, excellent heat resistance is achieved. When the amount is 10 parts by mass or less, storage stability is improved.
[0066] (organic solvent) The curable resin composition of the present invention may contain an organic solvent for the purpose of adjusting the viscosity when preparing the composition or when applying it to a substrate or a carrier film. Examples of the organic solvent include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. These organic solvents can be used alone or in combination of two or more.
[0067] (Other optional ingredients) The curable resin composition of the present invention may further contain other curing components and additives known and commonly used in the field of electronic materials. Examples of other curing components include cyanate ester resins, active ester resins, maleimide compounds, and alicyclic olefin polymers. Examples of other additives include thermal polymerization inhibitors, ultraviolet absorbers, silane coupling agents, plasticizers, flame retardants, antistatic agents, antioxidants, antibacterial and antifungal agents, antifoaming agents, leveling agents, thickeners, adhesion promoters, thixotropy-imparting agents, photoinitiator assistants, sensitizers, thermoplastic resins, organic fillers, release agents, surface treatment agents, dispersants, dispersion assistants, surface modifiers, stabilizers, and phosphors.
[0068] The curable resin composition of the present invention may be used in the form of a dry film or in a liquid form. When used in a liquid form, it may be a one-component type or a two-component or more-component type.
[0069] Next, the dry film of the present invention has a resin layer obtained by applying the curable resin composition of the present invention to a carrier film and drying it. To form the dry film, the curable resin composition of the present invention is first diluted with the organic solvent described above to adjust the viscosity to an appropriate level, and then coated to a uniform thickness on the carrier film using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, or the like. The coated composition is then typically dried at a temperature of 40 to 130°C for 1 to 30 minutes to form a resin layer. There are no particular limitations on the coating thickness, but it is generally selected appropriately from a range of 3 to 150 μm, preferably 5 to 60 μm, in terms of the film thickness after drying.
[0070] The carrier film may be a plastic film, such as a polyester film such as polyethylene terephthalate (PET), a polyimide film, a polyamideimide film, a polypropylene film, or a polystyrene film. There are no particular restrictions on the thickness of the carrier film, but it is generally selected appropriately in the range of 10 to 150 μm, and more preferably in the range of 15 to 130 μm.
[0071] After forming a resin layer made of the curable resin composition of the present invention on a carrier film, it is preferable to further laminate a peelable cover film on the surface of the resin layer for the purpose of preventing dust from adhering to the surface of the resin layer. As the peelable cover film, for example, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, surface-treated paper, etc. can be used. The cover film may be any film as long as the adhesive strength between the resin layer and the carrier film is smaller when the cover film is peeled off.
[0072] In the present invention, the curable resin composition of the present invention may be applied to the cover film and dried to form a resin layer, and then a carrier film may be laminated on the surface of the resin layer. That is, in the present invention, when producing a dry film, either a carrier film or a cover film may be used as the film to which the curable resin composition of the present invention is applied.
[0073] The printed wiring board of the present invention has a cured product obtained from the resin layer of the curable resin composition or dry film of the present invention. For example, a method for producing the printed wiring board of the present invention involves adjusting the viscosity of the curable resin composition of the present invention using the organic solvent described above to a coating method suitable for the coating method, applying it to a substrate by a method such as dip coating, flow coating, roll coating, bar coating, screen printing, or curtain coating, and then evaporating and drying (pre-drying) the organic solvent contained in the composition at a temperature of 60 to 100°C to form a tack-free resin layer. In the case of a dry film, the resin layer is attached to the substrate using a laminator or the like so that the resin layer contacts the substrate, and then the carrier film is peeled off to form a resin layer on the substrate.
[0074] The substrates include printed wiring boards and flexible printed wiring boards with circuits already formed using copper or the like, as well as copper-clad laminates for high-frequency circuits made from materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven cloth epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluororesin, polyethylene, polyphenylene ether, polyphenylene oxide, cyanate, etc., including copper-clad laminates of all grades (FR-4, etc.), as well as metal substrates, polyimide film, PET film, polyethylene naphthalate (PEN) film, glass substrates, ceramic substrates, wafer plates, etc.
[0075] The volatilization drying carried out after application of the curable resin composition of the present invention can be carried out using a hot air circulation drying oven, an IR oven, a hot plate, a convection oven, or the like (a method in which hot air in a dryer equipped with a heat source of an air heating method using steam is brought into countercurrent contact with the substrate, or a method in which hot air is blown onto the substrate from a nozzle).
[0076] After forming a resin layer on a substrate, the resin layer is selectively exposed to active energy rays through a photomask with a predetermined pattern, and the unexposed areas are developed with a dilute alkaline aqueous solution (e.g., a 0.3 to 3% by mass aqueous solution of sodium carbonate) to form a pattern of a cured product. The cured product is then irradiated with active energy rays and then heat-cured (e.g., at 100 to 220°C), or is then irradiated with active energy rays after heat-curing, or is heat-cured alone to form a final cured film with excellent properties such as adhesion and hardness. When the curable resin composition of the present invention contains a photobase generator, it is preferable to heat the composition after exposure and before development. The heating conditions after exposure and before development are preferably, for example, heating at 60 to 150°C for 1 to 60 minutes.
[0077] The exposure device used for the above-mentioned active energy ray irradiation may be a device equipped with a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, or the like, and capable of irradiating ultraviolet rays in the range of 350 to 450 nm. Furthermore, a direct imaging device (for example, a laser direct imaging device that directly draws an image with a laser based on CAD data from a computer) may also be used. The lamp or laser light source of the direct imaging device may have a maximum wavelength in the range of 350 to 450 nm. The exposure dose for image formation varies depending on factors such as the film thickness, but is generally 10 to 1,000 mJ / cm. 2 , preferably 20 to 800 mJ / cm 2 The range may be:
[0078] The developing method may be a dipping method, a shower method, a spray method, a brush method, or the like, and the developing solution may be an aqueous alkali solution such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, or an amine.
[0079] The curable resin composition of the present invention is preferably used to form a cured film on a printed wiring board, more preferably to form a permanent coating film, and even more preferably to form a solder resist, an interlayer insulating layer, or a coverlay. Furthermore, the curable resin composition of the present invention can provide a cured product that is excellent in appearance and surface smoothness even when thin, and has excellent sensitivity and resolution, so it can be preferably used to form a permanent coating film (particularly solder resist) for a printed wiring board that requires high reliability in a thin film, such as a package substrate, especially for FC-BGA.
[0080] In particular, the curable resin composition of the present invention can be suitably used to form a thin film, preferably a cured film having a thickness of 3 to 40 μm, more preferably 5 to 30 μm. [Example]
[0081] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following, "parts" and "%" are all by mass unless otherwise specified.
[0082] (Synthesis of alkali-soluble resin A-1) Into an autoclave equipped with a thermometer, a nitrogen / alkylene oxide inlet, and a stirrer, 119.4 parts of cresol novolac resin (Shonol CRG-951 manufactured by Aica Kogyo Co., Ltd., OH equivalent: 119.4), 1.19 parts of potassium hydroxide, and 119.4 parts of toluene were introduced, and the system was purged with nitrogen while stirring, and heated to a temperature of 125-132°C and 0-4.8 kg / cm. Next, 63.8 parts of propylene oxide were gradually added dropwise, and the temperature was raised to 125-132°C and 0-4.8 kg / cm. 2The mixture was reacted at 100°C for 16 hours. The mixture was then cooled to room temperature, and 1.56 parts of 89% phosphoric acid was added to the reaction solution to neutralize the potassium hydroxide. This resulted in a propylene oxide reaction solution of novolac cresol resin with a nonvolatile content of 62.1% and a hydroxyl value of 182.2 mg KOH / g (307.9 g / eq.). This solution contained an average of 1.08 moles of propylene oxide added per equivalent of phenolic hydroxyl group. 293.0 parts of the resulting propylene oxide reaction solution of novolac cresol resin, 43.2 parts of acrylic acid, 11.53 parts of methanesulfonic acid, 0.18 parts of methylhydroquinone, and 252.9 parts of toluene. A reactor equipped with a stirrer, thermometer, and air inlet tube was then introduced. Air was blown in at a rate of 10 ml / min, and the mixture was stirred and reacted at 110°C for 12 hours. The water produced by the reaction was distilled as an azeotrope with toluene, and 12.6 parts of water were distilled off. The mixture was then cooled to room temperature, neutralized with 35.35 parts of 15% aqueous sodium hydroxide, and then washed with water. The toluene was then removed by distillation using an evaporator, while being replaced with 118.1 parts of diethylene glycol monoethyl ether acetate, to obtain a novolac acrylate resin solution. Next, 332.5 parts of the resulting novolac acrylate resin solution and 1.22 parts of triphenylphosphine were introduced into a reactor equipped with a stirrer, thermometer, and air inlet tube. Air was blown in at a rate of 10 ml / min. While stirring, 60.8 parts of tetrahydrophthalic anhydride was gradually added. The mixture was reacted at 95-101°C for 6 hours, cooled, and then discharged. Thus, a solution of acrylate resin A-1 with a solids content of 65% and an acid value of 87.7 mgKOH / g of solids was obtained.
[0083] (Synthesis of alkali-soluble resin A-2) A flask equipped with a condenser and a stirrer was charged with 456 parts of bisphenol A, 228 parts of water, and 649 parts of 37% formalin. While maintaining the temperature below 40°C, 228 parts of 25% aqueous sodium hydroxide was added. The reaction was continued for 10 hours at 50°C. After the reaction was completed, the mixture was cooled to 40°C and neutralized to pH 4 with 37.5% aqueous phosphoric acid while maintaining the temperature below 40°C. The mixture was then allowed to stand and the aqueous layer was separated. After separation, 300 parts of methyl isobutyl ketone was added and uniformly dissolved. The mixture was then washed three times with 500 parts of distilled water. Water and solvent were removed under reduced pressure at a temperature below 50°C. The resulting polymethylol compound was dissolved in 550 parts of methanol to obtain 1230 parts of a methanol solution of the polymethylol compound. A portion of the resulting methanol solution of the polymethylol compound was dried at room temperature in a vacuum dryer, revealing a solids content of 55.2%. 500 parts of the resulting methanol solution of the polymethylol compound and 440 parts of 2,6-xylenol were charged and homogeneously dissolved at 50°C. After homogeneous dissolution, methanol was removed under reduced pressure at a temperature below 50°C. 8 parts of oxalic acid was then added, and the reaction was carried out at 100°C for 10 hours. After completion of the reaction, distillate was removed under reduced pressure at 180°C and 50 mmHg, yielding 550 parts of novolak resin A. Furthermore, 130 parts of the above novolak resin A, 2.6 parts of a 50% aqueous sodium hydroxide solution, and 100 parts of toluene / methyl isobutyl ketone (mass ratio = 2 / 1) were charged into an autoclave equipped with a thermometer, a nitrogen introducing device / alkylene oxide introducing device, and a stirrer. The system was purged with nitrogen while stirring, and then heated to 150°C and 8 kg / cm. 2 45 parts of ethylene oxide was gradually introduced and the reaction was carried out at a gauge pressure of 0.0 kg / cm. 2The reaction mixture was stirred for approximately 4 hours until the reaction mixture reached a final concentration, after which it was cooled to room temperature. 3.3 parts of 36% aqueous hydrochloric acid was added to the reaction mixture and mixed to neutralize the sodium hydroxide. The neutralized reaction product was diluted with toluene, washed with water three times, and then the solvent was removed using an evaporator to obtain an ethylene oxide adduct of novolak resin A with a hydroxyl value of 175 g / eq. This product had an average of 1 mole of ethylene oxide added per equivalent of phenolic hydroxyl group. 175 parts of the ethylene oxide adduct of novolak resin A, 50 parts of acrylic acid, 3.0 parts of p-toluenesulfonic acid, 0.1 parts of hydroquinone monomethyl ether, and 130 parts of toluene were charged into a reactor equipped with a stirrer, thermometer, and air inlet tube. The mixture was stirred while blowing in air, heated to 115°C, and reacted for an additional 4 hours while distilling off the water produced by the reaction as an azeotrope with toluene. The mixture was then cooled to room temperature. The resulting reaction solution was washed with a 5% aqueous NaCl solution, and the toluene was removed by distillation under reduced pressure. Diethylene glycol monoethyl ether acetate was then added to obtain an acrylate resin solution with a solid content of 68%. Next, 312 parts of the obtained acrylate resin solution, 0.1 parts of hydroquinone monomethyl ether, and 0.3 parts of triphenylphosphine were charged into a four-neck flask equipped with a stirrer and reflux condenser. The mixture was heated to 110°C, 45 parts of tetrahydrophthalic anhydride was added, and the mixture was allowed to react for 4 hours. After cooling, the mixture was removed. The carboxyl group-containing photosensitive resin thus obtained had a nonvolatile content of 72% and a solids acid value of 65 mgKOH / g. Hereinafter, this carboxyl group-containing photosensitive resin solution will be referred to as A-2 varnish.
[0084] (Synthesis of alkali-soluble resin A-3) A flask equipped with a condenser and a stirrer was charged with 456 parts of bisphenol A, 228 parts of water, and 649 parts of 37% formalin. While maintaining the temperature below 40°C, 228 parts of 25% aqueous sodium hydroxide was added. The reaction was continued for 10 hours at 50°C. After the reaction was completed, the mixture was cooled to 40°C and neutralized to pH 4 with 37.5% aqueous phosphoric acid while maintaining the temperature below 40°C. The mixture was then allowed to stand and the aqueous layer was separated. After separation, 300 parts of methyl isobutyl ketone was added and uniformly dissolved. The mixture was then washed three times with 500 parts of distilled water. Water and solvent were removed under reduced pressure at a temperature below 50°C. The resulting polymethylol compound was dissolved in 550 parts of methanol to obtain 1230 parts of a methanol solution of the polymethylol compound. A portion of the resulting methanol solution of the polymethylol compound was dried at room temperature in a vacuum dryer, revealing a solids content of 55.2%. 500 parts of the resulting methanol solution of the polymethylol compound and 440 parts of 2,6-xylenol were charged and homogeneously dissolved at 50°C. After homogeneous dissolution, methanol was removed under reduced pressure at a temperature below 50°C. 8 parts of oxalic acid was then added, and the reaction was carried out at 100°C for 10 hours. After completion of the reaction, distillate was removed under reduced pressure at 180°C and 50 mmHg, yielding 550 parts of novolak resin A. Furthermore, 130 parts of the above novolak resin A, 2.6 parts of a 50% aqueous sodium hydroxide solution, and 100 parts of toluene / methyl isobutyl ketone (mass ratio = 2 / 1) were charged into an autoclave equipped with a thermometer, a nitrogen introducing device / alkylene oxide introducing device, and a stirrer. The system was purged with nitrogen while stirring, and then heated to 150°C and 8 kg / cm. 2 45 parts of ethylene oxide was gradually introduced and the reaction was carried out at a gauge pressure of 0.0 kg / cm. 2The reaction mixture was stirred for approximately 4 hours until the reaction mixture reached a final concentration, after which it was cooled to room temperature. 3.3 parts of a 36% aqueous solution of hydrochloric acid was added to the reaction mixture and mixed to neutralize the sodium hydroxide. The neutralized reaction product was diluted with toluene, washed with water three times, and then the solvent was removed using an evaporator to obtain an ethylene oxide adduct of novolak resin A with a hydroxyl value of 175 g / eq. This product had an average of 1 mole of ethylene oxide added per equivalent of phenolic hydroxyl group. 175 parts of the ethylene oxide adduct of novolak resin A, 75 parts of methacrylic acid, 3.0 parts of p-toluenesulfonic acid, 0.1 parts of hydroquinone monomethyl ether, and 130 parts of toluene were placed in a reactor equipped with a stirrer, thermometer, and air inlet tube. The mixture was stirred while blowing in air, heated to 115°C, and reacted for an additional 4 hours while distilling off the water produced by the reaction as an azeotrope with toluene. The mixture was then cooled to room temperature. The resulting reaction solution was washed with 5% NaCl aqueous solution, and the toluene was removed by distillation under reduced pressure. Diethylene glycol monoethyl ether acetate was then added to obtain an acrylate resin solution with a solid content of 68%. This acrylate resin solution will be referred to as resin solution A-3 hereinafter.
[0085] (Synthesis of spherical silica) An inorganic filler was obtained by mixing and dispersing 70 g of spherical silica (SFP-30M manufactured by Denka) and 30 g of PMA (propylene glycol monomethyl ether acetate) as a solvent.
[0086] [Examples and Comparative Examples] The components were blended in the proportions (parts by mass) shown in Table 1 according to the formulation, and the blended mixture was premixed in a stirrer and then kneaded in a bead mill to prepare curable resin compositions. The blend amounts in the table indicate the solid content (non-volatile content).
[0087] (Dry film preparation) The curable resin composition prepared above was applied to a PET film using an applicator so that the resin layer would have a predetermined thickness after drying, and then dried at 80° C. for 30 minutes to obtain a dry film.
[0088] (transmittance) A dry film with a resin layer thickness of 20 μm after drying was prepared according to the method described above (Preparation of Dry Film). The dry film with a resin layer thickness of 20 μm was laminated onto a 2 mm thick glass substrate, and the PET film was peeled off. The absorbance was then measured using a V-670 spectrophotometer.
[0089] (Concealment) Dry films with resin layer thicknesses of 20 μm and 25 μm after drying were prepared according to the method described above (Dry Film Preparation). Next, 18 μm copper foil was subjected to CZ processing (roughening treatment) at an etching rate of 1 μm using MEC Corporation's MEC Etch Bond CZ-8101, and then further treated with MEC Corporation's MEC Etch Bond CL-8300 for rust prevention. Each dry film was laminated to a printed wiring board with a 17 μm thick Cu layer and a comb-shaped pattern with an L / S = 12 μm / 13 μm. The entire surface was exposed to UV light using an Oak Manufacturing HMW680GW (metal halide lamp, scattered light) at an optimal exposure dose of 800 mJ. After peeling off the PET film, the film was further irradiated with UV light at an integrated exposure dose of 1000 mJ, followed by curing at 160°C for 60 minutes in a thermal circulation box furnace (post-cure). The printed wiring board having the resulting cured film was visually evaluated for its ability to conceal the circuit. ◎: The Cu circuit is completely invisible in both the 20 μm and 25 μm cured films. ◯: The Cu circuit is visible through the 20 μm cured film, but is completely invisible through the 25 μm cured film. ×: The Cu circuit is visible through both the 20 μm and 25 μm cured films.
[0090] (resolution) A dry film with a 20 μm thick resin layer was prepared according to the method described above (Dry Film Preparation). A 35 μm thick copper foil was CZ-treated (roughened) at an etching rate of 1 μm using MEC Etch Bond CZ-8101 (manufactured by MEC Corporation), and then a 34 μm thick copper foil was rust-proofed using MEC Etch Bond CL-8300. The dry film with a 20 μm thick resin layer was laminated onto the copper foil and exposed to light using a projection exposure system UFX-2223M-APU01 (which blocks wavelengths longer than i-line) to produce an aperture pattern with a diameter of 40 to 350 nm. The PET film was peeled off and developed with a 1.0 wt% aqueous sodium carbonate solution. The smallest aperture diameter that could be formed was confirmed using an SEM. ○: Minimum diameter is 40 μm or less ×: Minimum diameter is over 40 μm
[0091] (Color change confirmation test) A dry film with a 20 μm thick resin layer was prepared according to the method described above (Dry Film Preparation). A 35 μm thick copper foil was CZ-treated (roughened) at an etching rate of 1 μm using MEC Etch Bond CZ-8101 (manufactured by MEC Corporation), and then a 34 μm thick copper foil was rustproofed using MEC Etch Bond CL-8300. The dry film with a 20 μm thick resin layer was then laminated onto a substrate. The entire surface was exposed to light using an Oak Manufacturing HMW680GW (metal halide lamp, scattered light) at an optimal exposure dose of 800 mJ. After peeling off the PET film, the film was further irradiated with ultraviolet light at an integrated exposure dose of 1000 mJ. The test to confirm the change in color tone was carried out on the substrate after irradiating it with ultraviolet light in a thermal circulation box furnace under two conditions: 150°C, 60 minutes of post-cure, and 170°C, 60 minutes of post-cure. The color was measured in SCI mode using a Konica Minolta CM-2600d colorimeter. * a * b * The measurement was carried out by the method.
[0092] [Table 1]
[0093] The notes in the headings of Table 1 are as follows: *1: Alkali-soluble resin A-1 synthesized above *2: Alkali-soluble resin A-2 synthesized above *3: Alkali-soluble resin A-3 synthesized above *4: Neomer DA-600 manufactured by Sanyo Chemical Industries, Ltd. *5: BASF Japan Laromer LR8863 *6: DIC N-870-75EA *7: NC-3000H manufactured by Nippon Kayaku Co., Ltd. *8: DIC HP-7200L *9:CI Pigment red 149 *10:CI Pigment yellow 147 *11: Phthalocyanine blue (CI Pigment blue 15) *12: Carbon black *13: Sakai Chemical Industry Co., Ltd. B-30 *14: Spherical silica synthesized above *15: Omnirad TPO H manufactured by IGM Resins, an acylphosphine oxide photopolymerization initiator *16: JMT-784 manufactured by DKSH Japan, titanocene photopolymerization initiator *17: Melamine *18:DICY (Dicyandiamide) *19: Kawasaki Kasei Kinopower QS-30
[0094] From the results shown in the above table, it can be seen that the curable resin composition of the present invention is excellent in hiding power and resolution. In contrast, Comparative Example 1 had poor results in the evaluation of hiding power. Comparative Examples 2 and 3 had poor results in the evaluation of resolution. Comparative Example 4 had poor results in the evaluation of hiding power. Comparative Examples 5, 6, and 7 had poor results in the evaluation of resolution. Furthermore, for Examples 1 to 4 and Comparative Example 3, changes in color tone before and after heating were observed. Note that Comparative Examples 1 and 4 had poor results in the evaluation of hiding power, and Comparative Examples 2, 5, 6, and 7 had poor results in the evaluation of resolution, so no changes in color tone were observed. As a result, Examples 1 to 4 showed little change in color tone before and after heating, whereas Comparative Example 3 showed a greater change in color tone than Examples 1 to 4. Furthermore, although not shown in the table, a composition was prepared as Comparative Example 8 in which the components other than the pigment were blended in the same amounts as in Comparative Example 2, but the black, yellow, and red pigments were not included, and only blue pigment was blended in at 1.89 parts by mass. When the resolution of this Comparative Example 8 was evaluated, it was improved to 30 μm, but the evaluation result of the hiding power was ×, so no other evaluations were performed.
Claims
1. A curable resin composition comprising (A) an alkali-soluble resin, (B) a photopolymerization initiator, (C) a thermosetting resin, and (D) a colorant, the curable resin composition being formed on copper having a CZ-treated surface, The (D) colorant contains a red colorant, a blue colorant, a yellow colorant and a black colorant, The content of the (D) colorant is, relative to 100 parts by mass of the solid content of the (A) alkali-soluble resin, 0.60 to 2.00 parts by mass of the red colorant, 1.10 to 2.45 parts by mass of the blue colorant, 0.01 to 0.08 parts by mass of the yellow colorant, and 0.01 to 0.04 parts by mass of the black colorant.
2. The curable resin composition according to claim 1, wherein the transmittance of a dry coating film (film thickness 20 μm) of the curable resin composition formed on a glass substrate having a thickness of 2 mm is 5% or more at a wavelength of 365 nm, 30 to 50% at a wavelength of 430 nm, 28 to 45% at a wavelength of 530 nm, and 12% or less at a wavelength of 720 nm.
3. A dry film comprising a resin layer obtained from the curable resin composition according to claim 1 or 2.
4. A cured product obtained by curing the curable resin composition according to claim 1 or 2 or the resin layer of the dry film according to claim 3.
5. A printed wiring board comprising the cured product according to claim 4.
Citation Information
Patent Citations
Curable resin composition, dry film, cured article, and printed wiring board
JP2021170054A
Resist ink composition
JP1986243869A